THE RELATIONSHIP BETWEEN STUDENTS' INTEREST IN LEARNING AND MATHEMATICS LEARNING OUTCOMES - Harefa, Darmawan (Universitas Nias Raya, 2023)
This study aims to determine a positive and significant relationship as well as an influence between students' interest in learning and their mathematics learning outcomes. The research method used in this study is quantitative research with a correlational approach. The population in this study consists of all eighth-grade students at SMP Negeri 1 Toma, totaling 65 students. The sampling technique used is total sampling, meaning the entire population is used as the sample. The instruments in this study include closed-ended questionnaires and students' mathematics learning outcomes in the form of even semester final exam scores (UKK). Data analysis techniques involve describing the data, correlational analysis, coefficient of determination, and hypothesis testing. The results of this study show that there is a positive and significant relationship between students' interest in learning and their mathematics learning outcomes, and there is also an influence of students' interest in learning on their mathematics learning outcomes. It can be concluded that 1) because students have a sense of enjoyment, interest, and a high desire to learn that they perceive as beneficial and satisfying, and 2) students feel comfortable, are aware of the benefits of learning, and understand the learning objectives, which makes them interested and leads to an improvement in learning outcomes.